Coping with Culture Shock: Communication Patterns of Non-PMDG Students at UNIDA Gontor - Abdillah, Muzakky; Pia Wulandari, Maulina; Nasution, Zulkarnain (Universitas Darussalam Gontor, 2024)
Abstract This research aims to analyze the phenomenon of culture shock experienced by Non-KMI (Kulliyatul Mu›allimin Al-Islamiyah) students at Darussalam Gontor University (UNIDA Gontor). Non-KMI students, who come from non-Islamic boarding school backgrounds, face great challenges in adapting to an Islamic boarding school-based campus environment, where Arabic and English are used as the main languages, and high discipline is an integral part of campus life. Using an exploratory qualitative approach, this research explores the adaptation experiences of Non-KMI students by focusing on emotional, behavioral and cognitive aspects. Data was collected through in-depth interviews, participant observation, and documentation related to academic and social life on campus. The research results showed that non-KMI students experienced culture shock in the form of anxiety, confusion, and changes in perception of the dominant cultural values at UNIDA Gontor. Behavioral aspects also include difficulties in adapting to congregational worship procedures and the use of Arabic in daily communication. This research identified several factors that cause culture shock, such as differences in communication patterns, lifestyle, and lack of social support from the surrounding environment. However, through effective communication strategies, such as building intercultural communication skills and increasing social interaction, Non-KMI students can adapt better to campus culture. This research provides practical insights to support the adaptation process of Non-KMI students in Islamic boarding school-based educational environments and offers suggestions for strengthening cultural orientation and cross-cultural interaction programs at universities. Keywords: Communication Patterns; Cultural Adaptation; Intercultural Communication